Transforming food environments to deliver healthy diet options: Economic rationale and policy drivers - Mockshell, Jonathan Yaw; Martey, Edward; Etwire, Prince M.; Khoury, Colin K.; Prager, Steven D. (International Center for Tropical Agriculture, 2019)
The second Sustainable Development Goal (SDG) envisions comprehensive global food security and improved nutrition by 2030. This is a major challenge, with persisting undernutrition and micronutrient deficiencies in multiple regions, and the increase in excessive consumption of macronutrients contributing to overweight and obesity, heart disease, and Type 2 diabetes even in low- and middle-income countries. While improvements are needed throughout current food systems, the food retail environment (FRE) in developing countries remains an underexplored link between production systems and consumers in food and nutrition security programs. This study examines the economic rationale of actors in the food retail environment and suggests policy options to nudge the food environment to deliver a healthier basket of foods. The policy options are classified into personal changes, private sector actions, and public sector initiatives. We argue that for a comprehensive transformation of the food retail environment to deliver healthier food options, private, public sector initiatives, and consumer awareness all require urgent action.